The Assessment of CSR Regulations Implementation on the Midship Strength and Structural Weight of 77.500 DWT Bulk Carrier - Zakki, Ahmad Fauzan (The Indonesian Journal of Naval Architecture, 2013)
Since April 1st 2006, all of the ships that built must comply with the common structural rules. As the consequences of this condition the scantling of the ship will be increased. This paper will explain about the influence of the CSR rules implementation to the midship strength and structural weight of 77.500 DWT Bulk Carrier. The comparisons of two finite element models will be made to distinguish the effect of scantling modifications to the midship strength and the weight of the ship structures. The results show that the steel weight has been increased 4.74 % higher than the prior ship. The critical condition is the harbor-1 condition with the maximum plate stress induced by SWBM is 96.6 MPa; The Maximum Bar Stress is 84.7 MPa. The conclusion states that the CSR regulations standard not significantly different with the DNV standard for the Midship Strength performance. It could be actually explains that the increment of the plate thickness only for the corrosion allowance.